The Impact of Technological Development and Modern Techniques on Interior Design - Obeidat, Ahmad Mahmoud; Al- Shar'a , Raed (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed to identify the impact of using technological development and modern techniques of interior design on how interior spaces are treated via the employment of modern techniques in interior spaces to meet the needs and demands of people as well as to ensure the maximum use spaces since the use of technology and modern techniques- based design in interior space determinants help solve the recurrent problems in interior spaces. Method: In this study, the researcher used the descriptive analytical method to examine the importance of using advanced technology and modern techniques in the field of interior design in the age of information revolution. Results: The study showed that modern interior design helps to renew and upgrade the space’s shape easily in accordance with the client’s functional requirements and showed that the interior design’s dazzling factors contribute to attracting more clients. It showed that technology and modern techniques-based design helps reduce the problems connected to interior design and presents an innovative and meaningful design that is easily learnt, practiced, and used. The study showed that technology and modern techniques-based design reinforces the positive aspects of design through presenting an entertaining and fun design which the user may enjoy through the employment of different senses and betters the user’s experience. Conclusion: The study recommends keeping pace with technological development in the field of interior design. The research also highlights the necessity of integrating modern techniques in interior design in the curriculums offered by the faculties of design and architecture.